Dispersion Of Iron Oxide Nanoparticles On Oxide Nanotube For Nanocatalyst System - Anwar, Dede Miftahul (2014)
TiO2 nanotube arrays (TNTs) and ZrO2 nanotube arrays (ZNTs) were NH4F at 60 V for 30 min. For the formation of nanotubes; oxidation and dissolution have been identified as two most important processes. The dissolution process occurs at the surface of the oxide, inside the pores and in between pores. Comparing TNT and ZNT; it appears ZNTs are longer with smaller diameter and thinner wall compared to TNT. Even though the anodic layer on Zr has higher value of polarization resistance (~3.92 kQ) than TNTs (-7.82 kQ) the dissolution rate of Z1O2 is lower (0.11 mm/year) compared to TNTs (0.416 mm/year), making TNTs are shorter. The dissolution rate of oxide on Ti and Zr is also different resulting in different dimensions. Photocurrent and charge distribution measurement exhibited excellent ability of photogenerated free charge-carriers flow in TNTs but low for ZNTs. Therefore TNTs was need as a cathode to electrodeposit iron oxide. The formation of TNTs was further studied by the use of was suitable to be used as a template for the electrodeposition of iron oxide. For the electrodeposition lectrolyte consisting of 0.02 M FeCh bFhO + DI water was used. Parameters studied for this process included voltage, concentration of electrolyte and the effect of additives in the electrolyte.